Use of Ice Cream Stick Props to Improve Mathematics Learning Outcomes Addition and Subtraction Material For Grade I Students of MI Hidayatul Mubtadiin New - Samirih, Samirih (Jurnal Multidisiplin Indonesia, 2024)
The background of this research was – low mathematics calculation operations, addition, and subtraction in mathematics subjects found in the learners at Islamic Primary School Hidayatul Mubtadiin New Kedungwungu. This Classroom Action Research applied the Kemmis & Taggar model, starting from planning, acting, observing, and reflecting to improve the mathematics learning outcomes of the learners. The population consisted of first graders of Islamic Primary School Hidayatul Mubtadiin New who could not do addition and subtraction operations. The population also became the research sample that received mathematics learning with ice cream stick properties for three cycles. The researchers collected the data using Observation, tests, documentation, and interviews to analyze descriptively. The results showed increased learning outcomes for the learners after using the ice cream stick property for learning mathematics within the materials of addition and subtraction. The results showed that the learners could reach the minimum mastery completion on each cycle. In cycle I, six learners, or 30% of learners, passed the minimum completion. In cycle II, the numbers increased to 13 learners, 65%. Then, in cycle III, the numbers improved to 17 learners, 85%. From the results, the researchers suggested schools provide proper property facilities and infrastructure for the teachers. The researchers also recommend that teachers apply the ice cream stick property to mathematics learning. The teachers must also consider the learners' skills.